Capacity building of civil servants in Myanmar - NAN MYINT, Mary (KDI School, 2016)
Most of the governments in developed countries emphasized on the capacity development of their human resource to deliver the quality service. Capacity Building trainings are the most effective way to improve the ability and capacity of individuals and institutions, therefore, capacity building trainings should be a part of human resource development plan of any government. It is a means for capacity building training and could contribute to the efficiency and effectiveness of government functions. Myanmar is on the track of democracy transformation and government officials have to deal with new policies and strategies. The General Administration Department (GAD) is a backbone of the Myanmar administrative system and it performs a role of coordination among the different ministries. Given the complex functions performed by GAD, building the capacity of its officials needs to be given much attention. The, objective of this paper is to explore the basic functions of GAD and the curriculum used in the capacity building trainings of GAD officials. In this regards, primary and secondary data were collected from several sources and, the key needs were identified. This study found out that the curriculums are general task oriented rather than skills to perform the functions of the GAD. Moreover, the lack of the skill gap analysis before training and the lack of the evaluation of the effectiveness of the trainings are the key problems that need to be considered in developing an effective curriculum.
Thesis(Master) --KDI School:Master of Public Policy,2016